Chromium and cobalt in blood and serum in the surveillance of metal-on-metal hip implants - Scalici, Gianluca; Cirri, Nadia; Bellini, Irene; Benelli, Giovanni (Lo Scalpello - Journal, 2021)
Objective. The aim of this study is to evaluate the relationship between serum and whole blood chromium and cobalt levels in a group of patients with metal-on metal total hip arthroplasty (Depuy ASR™). A conversion formula was developed to allow adequate evaluation of patients and correctly interpret the measured value. Methods. The authors retrospectively reviewed a series of 150 patients and prospectively analysed 64 patients who satisfied inclusion criteria. We collected data by taking simultaneously sample of chromium and cobalt ionemia from blood and serum.Results. Statistical analyses revealed significant differences between chromium and cobalt values in serum and whole blood (p 0.007), but with a strong positive correlation for both chromium (r 0.927) and cobalt (r 0.935). The authors also calculated a conversion formula to convert whole blood ion levels into serum levels, Cr se = -0.32582 + 1.39018*Cr WB for chromium and Co se = 0.239637 + 0.804279* Co WB, for cobalt. Conclusions. The difference between serum and blood values of chromium and cobalt is highlighted in a strong positive correlation. The development of the conversion formula allows to better interpret laboratory data and improve care and monitoring of patients.